2010
DOI: 10.1016/j.childyouth.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mental health services for children and youth in the child welfare system: A focus on caregivers as gatekeepers

Abstract: Caregivers serve as gatekeepers for children while in the child welfare system, but few studies have focused on the caregiver and the factors that influence the use of mental health services for the children under their care. The purpose of this study was to examine the child’s mental health need, the caregiver’s level of stress, depression, and social support, and the utilization of mental health services by children using the three most common types of caregivers in the child welfare system (i.e., birth pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 40 publications
0
41
0
1
Order By: Relevance
“…The entry cohort (N=36,543) included all children, from birth to 17 years of age, who were placed in out-of-home care and spent at least 12 months in either kinship care or nonkinship foster placements during FY 2007-2008through FY 2009-2010. Of these children, 50% were male and their average age was 5 years (M = 4.79, SD = 5.21).…”
Section: Study Design and Samplementioning
confidence: 99%
“…The entry cohort (N=36,543) included all children, from birth to 17 years of age, who were placed in out-of-home care and spent at least 12 months in either kinship care or nonkinship foster placements during FY 2007-2008through FY 2009-2010. Of these children, 50% were male and their average age was 5 years (M = 4.79, SD = 5.21).…”
Section: Study Design and Samplementioning
confidence: 99%
“…One is that children who could not be discharged from out-of-home care sooner are those who have greater mental health needs and, therefore, they were more likely to receive mental health services and more likely to receive more expensive services, such as inpatient care. Others have suggested that foster parents as caregivers are more likely to see that the children in their care have access to mental health services than birth parents (Villagrana 2010). It is also possible that length of stay in out-of-home care is confounded with age, and it has been previously shown that age is positively associated with a significantly greater likelihood of mental health service utilizations (Garland et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Children in the child welfare system are generally supervised by their primary caregiver (i.e., birth parent, relative caregiver, or foster parent) and caregivers serve as gatekeepers for children while these children are in the child welfare system (Schneiderman & Villagrana, 2010;Villagrana, 2010), but no studies to date have focused on the factors that influence a caregiver's use of mental health services for the children under their care. This study focused on the caregiver's endorsement of barriers to mental health services to determine whether these factors are influential in the utilization of mental health services for the children under their care.…”
Section: Barriers To Mental Health Services By Caregivers In Communitmentioning
confidence: 99%
“…Because children generally do not seek mental health services for themselves (Schneiderman & Villagrana, 2010;Villagrana, 2010), one area that lacks attention, and may help explain the underutilization of mental health services by this population, is the influence that the caregiver has on a child's utilization of services. The extant literature in the field of mental health indicates that a person's perception, knowledge, and attitudes toward mental health and mental health services are significant predictors of mental health service utilization (Alvidrez, 1999;Constantine, 2002;Vega, Kolody, & Aguilar-Gaxiola, 2001).…”
mentioning
confidence: 98%